Effect of Deficit Sub-Surface Drip Irrigation on Growth Characteristics and Yield - Kamillo, Macham Barach Atem; Okwany, Romulus O.; Wambua, Raphael M. (International Journal For Research In Agricultural And Food Science, 2022)
The challenge of limited water availability for okra crop production due to a decrease in rainfall remains the main problem for many farmers in The Republic of South Sudan, which is exacerbated by effect of climate change. Climate change has a direct effect on the quality and quantity of water for irrigated agriculture. Thus, the reduction of okra crop sufficed for water requirement and water stress to okra crop, which leads to low yield. This study assessed the effect of deficit sub-surface drip irrigation on growth characteristics and yield response of okra crop under various crop water requirements. The controlled irrigation experiment was carried out at Egerton University Tatton Farm under a 20 m x 11 m shade located in sandy-loam soil. The study area was divided into 27 plots, each deficit block measuring 180 cm by 180 cm. Three water applications of deficit irrigation levels 50%, 75% and 100% of the Crop Water Requirements (CWR), were applied to the field. The drip laterals were laid on the soil surface. The spaghetti tubes were buried at 10 cm, 15 cm and 20 cm of depth below the soil surface. The setting of irrigation levels and drip depths were done in three replications. The study used Okra Clemson Spineless (Abelmoschus escullentus) (commonly called Finger Lady), based on agronomic practice. The soil moisture content was monitored at 100% irrigation levels by Tension-meters to determine the crop water requirement. The growth characteristics was affected by different levels of soil moisture content at placement depths. It was observed that, water deficit restricts the crop growth by decreasing the soil-water potential, resulting in reduced number of leaves, the plant height, pod diameter and pod height for some plants. The yield was also affected by different levels of soil moisture content where the least water supply condition (50% ETc) produced the average yield of about (0.03kg) at the top subsurface depth (10cm). And full water supply condition (100 % ETc) produced the lowest yield (0.028 kg) at 20cm placement depth. The result concluded with that the placement depth at 15 cm at 75 % and 10 cm at 50 % and 100 % of deficit irrigation water levels has positive significant effect in regarding of reducing the impact of evaporation losses through soil surface and thus allowing available water of being utilized by the crop at plant root zone.